2001
DOI: 10.1345/aph.10399
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns and Therapeutic Implications for Diabetic Hypertension in Bahrain

Abstract: The prescribing pattern of antihypertensives in diabetic hypertension differs in many instances from WHO/ISH guidelines, especially regarding the choice of antihypertensive drugs and their combinations. The appropriateness of antidiabetic drug choice is questionable in relation to the antihypertensive used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
5
25
0
Order By: Relevance
“…A similar study as ours by Al Khaja KA et al, concluded the same. 12 In triple drug therapy metformin along with sulfonylureas and DPP-4 inhibitors as add on therapy was the commonest combination prescribed followed by voglibose and pioglitazone. This does not correspond to the results by Haghighatpanah et al, showing voglibose being the commonest choice as add on therapy to metformin and glimepiride.…”
Section: Metforminmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study as ours by Al Khaja KA et al, concluded the same. 12 In triple drug therapy metformin along with sulfonylureas and DPP-4 inhibitors as add on therapy was the commonest combination prescribed followed by voglibose and pioglitazone. This does not correspond to the results by Haghighatpanah et al, showing voglibose being the commonest choice as add on therapy to metformin and glimepiride.…”
Section: Metforminmentioning
confidence: 99%
“…(Table 1) in contrast to study by Patel B et al, which also showed positive correlation of family history (35.1%) and hypertension (70.2%) as the commonest co-morbid condition. 12 Metformin (biguanide) has advantages over insulin secretagogues by decreasing excess hepatic gluconeogenesis without raising insulin levels. It seldom leads to hypoglycemia when used as a monotherapy.…”
mentioning
confidence: 99%
“…7,11,15,16,[18][19][20] Among the sulfonylureas, glimepiride was the most commonly prescribed drug along with metformin which is similar to studies. 10,18 Metformin is one of the safest and most cost effective drug compared to other drugs in terms of hypoglycaemia and decreasing BMI, hence this could be the most probable reason for this finding.…”
Section: Discussionmentioning
confidence: 57%
“…Most patients belonged in the age group of 41-50 yrs (40) followed by 51-60 yrs (20) age group. 98 drugs or 34.2% drugs were prescribed using their generic names.…”
Section: Male Femalementioning
confidence: 99%
“…Among the fixed drug combinations, the study found that combination of metformin and glimepride (6.85%) was the most commonly prescribed regimen followed by metformin + glibenclamide (4.57%), metformin + pioglitazone (2.86%), metformin + gliclazide (1.71%) and metformin + voglibose (1.71%) ( Table 4). Metformin + sitagliptin was the most common combination observed by Lisha Jeeny et al study, 16 while in Al Khaja KA et al, 2001 study, 17 metformin + sulfonylurea was the most common combination. Metformin was considered to be safer and cost effective drug over others in terms of hypoglycemia could be the probable reason for this finding.…”
mentioning
confidence: 89%